2000
DOI: 10.1128/cdli.7.4.536-539.2000
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to p52 and CM2 Recombinant Proteins in Primary Human Cytomegalovirus Infection with a Microparticle Agglutination Assay

Abstract: We evaluated the reactivities of sera against p52 and CM2 recombinant antigens of human cytomegalovirus (HCMV), coated on microparticles, for the differentiation of primary HCMV infection from an established infection. Two different test formats of the CMV Multiplex Copalis assay were evaluated. The 214 serum samples tested were immunoglobulin M (IgM) positive or equivocal by our reference assay. Reactivities against p52 and CM2 antigens were tested for sera from 37 patients with a well-documented seroconversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Few studies reported the validation of Copalis in comparison to standard ELISAs (17)(18)(19). In these studies, which were performed for the detection of CMV, syphilis, Anti-Ro/SSA and Anti-La/SSA, the assay had a sensitivity of 86, 92.2, 88.2 and 95.2% respectively using the Copalis second format; and a specificity of 81, 97.6, 93 and 97.6%.…”
Section: Coupled Particle Light Scattering (Copalis)mentioning
confidence: 99%
“…Few studies reported the validation of Copalis in comparison to standard ELISAs (17)(18)(19). In these studies, which were performed for the detection of CMV, syphilis, Anti-Ro/SSA and Anti-La/SSA, the assay had a sensitivity of 86, 92.2, 88.2 and 95.2% respectively using the Copalis second format; and a specificity of 81, 97.6, 93 and 97.6%.…”
Section: Coupled Particle Light Scattering (Copalis)mentioning
confidence: 99%
“…Detection of virus-specific IgM by ELISA, microagglutination, or immunoblotting is a widely used strategy to define HCMV infection as the etiology of disease in immunocompetent patients (15,17,23,26,31,32,48,49,51). In addition, screening for HCMV-specific IgM against defined viral antigens has been suggested as a method of improving the detection of maternal infection during pregnancy (8,28).…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of the amino acid sequences of the HCMV proteins pp150, pp65, pUL80a, pUL44, and pUL57 revealed short glycine-rich motifs of 5 to 13 aa in the carboxy-terminal part of pUL44 and the central parts of pUL57. pUL44 and pUL57 are contained in antigen preparations widely used for the design of commercially available HCMV IgM ELISAs and agglutination assays, as well as for the design of immunoblots assays (8,23,31,32,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Показано, что состав экспрессируемых вирусных белков отличается на разных стадиях CMV-инфекции (ЦМВИ). Исследование антител к индивидуальным антигенам ЦМВ позволяет уточнить фазу инфекции (первичную, хроническую, латентную), что нашло применение в клинической практике [3,14].…”
Section: Introductionunclassified